Utilization Pattern for Eculizumab Among Children With Hemolytic Uremic Syndrome - Ranabothu, Saritha; Brown, Clare C.; Blaszak, Richard; Millner, Rachel; Moore, Kristen Rice; Prodhan, Parthak (Frontiers in Pediatrics, 2021)
Background: Hemolytic uremic syndrome (HUS) is a complex disease with multi-organ involvement. Eculizumab therapy is recommended for the treatment of atypical hemolytic uremic syndrome (aHUS). However, there are few studies evaluating eculizumab therapy among children with HUS. The primary objectives of the study were to describe and identify factors associated with eculizumab therapy in children with HUS. Design/Methods: This large, retrospective, multi-center, cohort study used the Pediatric Health Information System (PHIS) database to identify the index HUS-related hospitalization among patients ≤ 18 years of age from September 23, 2011 through December 31, 2018. Multivariate analysis was used to identify independent factors associated with eculizumab therapy during or after the index hospitalization Results: Among 1,885 children included in the study, eculizumab therapy was noted in 167 children with a median age of 3.99 years (SD ± 4.7 years). Eculizumab therapy was administered early (within the first 7 days of hospitalization) among 65% of children who received the drug. Mortality during the index hospitalization among children with eculizumab therapy was 4.2% vs 3.0% without eculizumab therapy (p = .309). Clinical factors independently associated with eculizumab therapy were encephalopathy (odds ratio [OR] = 3.09; p ≤ .001), seizure disorder (OR = 2.37; p = .006), and cardiac involvement (OR = 6.36, p < .001). Conclusion(s): Only 8.9% of children received eculizumab therapy. Children who presented with neurological and cardiac involvement with severe disease were more likely to receive eculizumab therapy. Further prospective studies are suggested to confirm these findings